Visual search behaviors and decision-making of receiver in volleyball tossing and spiking - Umezaki, S.; Yoshida, M.; Mori, Y.; Kida, N. (The Japan Journal of Coaching Studies, 2021)
The purpose of this study was to clarify visual search behavior and decision time in continuous decision tasks of the toss direction and spike course in volleyball. Volleyball players, ball game players, and non-ball game players (10 in each group) wearing eye-movement trackers watched video images of combination attacks from three directions and made decision about whether the toss direction was left or right and the spike course was straight or cross. The results revealed the following:1) In comparison to ball game and non-ball game players, volleyball players had a faster decision time for toss direction and the spike course. Furthermore, volleyball players made excellent decision-making even in situations involving continuous decisions.2) Volleyball players have quiet eye characteristics. In other words, they gaze for long periods at the body, including the face, and torso of players, including setters and spikers who pass the ball.3) It was revealed that after deciding the toss direction, volleyball players quickly glance at the spiker before the spiker steps in with both his feet and decide the spike course from the opponent`s upper-body turn or arm swing.